THE INFLUENCE OF HYDROGEN ON THE PLASTIC PROPERTIES OF THE REINFORCING BARS - E. P. Baradyntseva; N. A. Glazunov; S. V. Stefanovich; O. V. Rogovtsova (Литьë и металлургия)
The research carried out in laboratory of metal science on detection of hydrogen presence in reinforcement depending on period of aging and reinforcement profile and also its influence on plastic properties of reinforcing bar is described in this article. The method of glycerine tests was applied for identification of hydrogen presence in finished reinforcing bar, the essence of which is in the fact that at gas emission from metal the bubbles stay too long on the surface of cross samples under glycerin layer. The revealed regularities enable to recommend actions for providing stable mechanical properties of the heat-strengthened reinforcement by creation of conditions for lowering of steel saturation with hydrogen, preventing thereby occurrence of hydrogen embrittlement of reinforcement on JSC «BMZ» – management company of holding «BMK».